Carotid angioplasty with cerebral protection - Miloševič, Zoran (Radiology and oncology (Ljubljana), 2002)
Background. Carotid endarterectomy (CF.A) is widely used in the management of high-rade carotid stenosis: It is a surgical procedure requiring general anaesthesia and is suitable only for lesions located at or close to the carotid bifurcation. It may develop complications, such as stroke, death, cranial nerve palsies, wound haematoma and cardiac complications. The risk of complications is increased in patients with recurrent carotid artery stenosis following CEA, in subjects undergoing radiotherapy to the neck, and in patients with cardiopulmonary disease. The drawbacks of CEA have led physicians to search for alternative treatment options. Carotid angioplasty and stenting (CAS) is less invasive than CEA. The method is particularly suitable for the treatment of recurrent stenosis after previous CEA and distalinternal artery stenosis, which is inaccessible for CEA. CAS does not cause cranial nerve palsies. Moreover, it does not require general anaesthesiaand causes lower morbidity and mortality in patients with severe cardiopulmonary disease. The complications of CAS include stroke due to distalimmobilisation of a plaque or thrombus dislodged during the procedure, abrupt vessel occlusion due to thrombosis, dissection or vasospasm, and restenosis due to intmal hyperplasia. CAS is a relatively new procedure; therefore, it is essential to establish its efficacy and safety before it is introduced widely into clinical practice. Patients and methods. In Slovenia, we have also started with carotid angioplasty by the study: Slovenian Carotid Angioplasty Study (SCAS). We performed CAS in 17 patients (12 males and 5 females) aged from 69 to 82 years. All patients were symptomatic with stenosisgreater than 70 %. 10 patients suffered transient ischemic attacks, 4 patients minor strokes and 3 patients amaurosis fugax. (Abstract truncated at 2000 characters)
Keywords: Angioplastika; Angioplasty; arterije; Carotid artery diseases; Cerebral infarction; cerebrovaskularne motnje; Izid zdravljenja; Karotidna arterija, bolezni; Možganski infarkt; Opornice; Prevention and control; Radiography; Stents; Surgery; therapy; Treatment outcome; zdravljenje